Dietary protein intake and PM2.5 on ovarian cancer survival: A prospective cohort study - He-Li Xu; Yi-Fan Wei; Qi Bao; Ya-Li Wang; Xiao-Ying Li; Dong-Hui Huang; Fang-Hua Liu; Yi-Zi Li; Yue-Yang Zhao; Xin-Xin Zhao; Qian Xiao; Song Gao; et al. (Ecotoxicology and Environmental Safety)
Background: Evolving evidence suggests both protein consumption and particulate matter less than 2.5 micrometers (PM2.5) might be related to ovarian cancer (OC) mortality. However, no epidemiological studies have explored their potential interaction. Objective: The objective of this study was to explore the association of dietary protein, PM2.5, and their interaction with the survival of OC patients. Methods: A prospective cohort study was carried out, which encompassed 658 newly diagnosed OC patients (18–79 years) residing in China. Dietary protein intakes were collected through a food frequency questionnaire examination, including total protein and protein from diverse sources. Average residential PM2.5 concentrations were evaluated using satellite-derived models. We calculated the hazard ratio (HR) and its 95 % confidence interval (CI) by adjusting for multiple variables using Cox proportional risk models. By assessing the relative excess risk due to interaction (RERI) arising from the interplay between PM2.5 exposure and dietary protein intake, we explored the additive interaction between the two. Multiplicative interaction was assessed through a cross-product interaction term. Results: During a median follow-up of 37.60 months, 123 deaths were documented. As for all-cause mortality, the multivariate-adjusted HRs (95 % CIs) in the highest vs. the lowest tertile were 0.57 (0.35–0.93), 0.60 (0.36–0.99), and 0.58 (0.37–0.90) for intakes of fish, egg, as well as fruit/vegetable protein, respectively (all P for trend < 0.05). A positive association between PM2.5 exposure and all-cause mortality was observed (HR=1.52; 95 % CI: 1.13–2.05, per interquartile range increment). Notably, dietary fish, egg, and fruit/vegetable protein modified these associations, as patients with lower intakes had significantly higher PM2.5-related mortality in the cohort (all P for interaction < 0.05). Conclusions: This study provides evidence linking the potential interactions between dietary fish, egg, and fruit/vegetable protein intake and PM2.5 exposure on all-cause mortality of OC patients. Our study demonstrates the importance of adherence to a certain protein diet in reducing PM2.5-related mortality risk for OC patients.